LABA BERSIH SEBAGAI VARIABEL INTERVENING ANTARA PENGARUH BIAYA OPERASIONAL DAN VOLUME PENJUALAN TERHADAP NET PROFIT MARGIN (Studi Kasus pada PT Aero Globe Indonesia Tahun 2007-2014) - Deden Edwar Yokeu Bernardin; Eva Nur Baeti (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2018)
Abstract: This research aims to analyze the influence of operating costs and sales volume to against net income of PT Aero Globe Indonesia, and to analyze how much effect from net income as intervening variabel of this research. The sampling technique used in this research is purposive sampling. The data in this research is secondary data which were obtained from 8 years financial statements years 2007 until 2014. The analyze methode of this research is path analysis. The result of this research show that operating cost and sales volume partially had negative significant effect to the net income. But after the research adding by the invervening variabel, the substructure 2 was show that operating cost, sales volume and net income simultaneously had positive significant effect to the net profit margin.Keywords: Operating Cost, Sales Volume, Net Income, Net Profit Margin